2020
DOI: 10.3390/en13236167
|View full text |Cite
|
Sign up to set email alerts
|

Wave Energy Extraction by Flexible Floaters

Abstract: We present a novel mathematical model to investigate the extraction of wave power by flexible floaters. The model is based on the method of dry modes, coupled with a matched eigenfunction expansion. Our model results compare satisfactorily with preliminary data obtained from a demonstrator device, developed at the University of Groningen. We show that the role of elasticity is to increase the number of resonant frequencies with respect to a rigid body, which has a positive effect on wave power output. The math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Loughborough University, in collaboration with Dutch company Ocean Grazer BV have recently proposed an innovative wave energy converter made by a floating flexible membrane, and connected to a multi-pump, multi-piston power take off system (MP 2 PTO). Michele et al [98] developed a novel mathematical model of the system, based on a potential-flow approach. Figure 17 shows a sketch of the conceptual model, where the floater has length 2L, submergence d, thickness h p and is connected to a series of linear PTO mechanisms (each with power take-off constant ν PTO ), over an ocean of depth h, above a platform of height c. Michele et al [98] showed that the bending elastic modes of the flexible floater enhance the energy extraction efficiency of the converter, with respect to the case of a rigid plate of the same dimensions.…”
Section: Flexible Floatermentioning
confidence: 99%
See 2 more Smart Citations
“…Loughborough University, in collaboration with Dutch company Ocean Grazer BV have recently proposed an innovative wave energy converter made by a floating flexible membrane, and connected to a multi-pump, multi-piston power take off system (MP 2 PTO). Michele et al [98] developed a novel mathematical model of the system, based on a potential-flow approach. Figure 17 shows a sketch of the conceptual model, where the floater has length 2L, submergence d, thickness h p and is connected to a series of linear PTO mechanisms (each with power take-off constant ν PTO ), over an ocean of depth h, above a platform of height c. Michele et al [98] showed that the bending elastic modes of the flexible floater enhance the energy extraction efficiency of the converter, with respect to the case of a rigid plate of the same dimensions.…”
Section: Flexible Floatermentioning
confidence: 99%
“…Michele et al [98] developed a novel mathematical model of the system, based on a potential-flow approach. Figure 17 shows a sketch of the conceptual model, where the floater has length 2L, submergence d, thickness h p and is connected to a series of linear PTO mechanisms (each with power take-off constant ν PTO ), over an ocean of depth h, above a platform of height c. Michele et al [98] showed that the bending elastic modes of the flexible floater enhance the energy extraction efficiency of the converter, with respect to the case of a rigid plate of the same dimensions. As an example, Figure 18 shows the behaviour of the Capture Factor versus the frequency of the incident waves, for an elastic and a rigid floater-Figure 18a,b, respectively.…”
Section: Flexible Floatermentioning
confidence: 99%
See 1 more Smart Citation
“…Michele et al. (2020) considered a 2-D flexible plate floating on the sea surface connected to a series of linear PTO units under the water. To investigate the wave power extraction by the device, a 2-D theoretical model was proposed based on the dry modes and eigenfunction matching method, and each PTO unit was modelled as a linear damper.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Michele et al. (2020) have used a distributed power take-off system connecting a floating elastic plate to the bed to generate power.…”
Section: Introductionmentioning
confidence: 99%